Development of environmental friendly chemistry practicum module for vocational high school - Lewi, Yosef Yonatan; Listyarini, Risnita Vicky (AIP conference proceedings, 2022)
The presence of a chemistry practicum module is important for the implementation of practicum in the vocational school. The practicum module is needed so practicum can run smoothly, learning objectives can be achieved, and reduce the risk of work accidents. On the other hand, the use of chemicals in the school is still quite large and the utilization of organic waste as practicum material is still limited. There is a need for an environmental friendly and integrated chemistry practicum procedure. Therefore, it is necessary to have an environmentally friendly chemistry practicum innovation for the subject of Organic Material Analysis in vocational high school. This research aims to develop an environmental friendly chemistry practicum module that utilizes fruit waste as practicum material for the production of ethanol, acetic acid and ethyl acetate. The integrated chemistry procedure is introduced in this practicum which uses products from the first practicum (ethanol) as a reactant for the production of the second practicum (acetic acid) and the third practicum (ethyl acetate). This is a research and development with ADDIE development model. The validity of the environmental friendly chemistry practicum module was assessed by validators; the effectiveness of the module was evaluated based on the score of students’ practicum reports; and the practicality of the module was evaluated from students’ responses using questionnaire. The environmental friendly chemistry practicum module is very valid criteria with an average percentage of 94.672%; very effective criteria based on the score of students’ reports with an average score of 87.515; and very practical with an average percentage of 90.555%. It can be concluded that the environmental friendly chemistry practicum module is valid, effective and practical. The environmental friendly chemistry practicum module can help the students for conducting experiments and promote students’ attitude concern towards the environment.